PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR GEOLOGI MAHASISWA UIN MAULANA MALIK IBRAHIM MALANG - Amin, Saiful (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
This research aims to examine the effect of Problem Based Leaning (PBL learning model to the student learning outcome. The research was conducted in Department of Social Sciences Education Faculty of Tarbiyah Education and Teacher ship UIN (State Islamic University) Maulana Malik Ibrahim Malang academic year 2014/2015. The research subject was students of second semester that follow geology class. Research method in this research using quasi experiment and the design is Non Equivalent Control Grow Data analysis used t-test technique (independent sample t-test). The research result showed that the average gain score of experimental class was high, which is 24.46 than control class, which is 13.21. Computation result of data t-test analysis to the PBL learning model was obtainai p-lerel wich smaller than 0.05 (px0.05) with significance 2 tailed 0.00. This computation result proved that PBL learning model affected to the learning outcome. Thus, it could be concluded that PBL learning model affected to the geology learning outcome of student in UIN Maulana Malik Ibrahim Malang.Keywords: Problem Based Learning (PBL), learning outcome